The Role of Financial Statements using the Camel Ratio Method to Assess Financial Performance at BNI Banks Registered at OJK - Enny Istanti; Achmad Daengs GS; Ruchan Sanusi; Sutopo Sutopo; RM Bramastyo KN; Syafi’i Syafi’i (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpuse: The aim is to determine the soundness of Bank Negara Indonesia (BNI in the 2017-2019 period, of which all four are State-Owned Enterprises (BUMN). Design/methodology/approach: The analysis carried out is a qualitative analysis using the CAMEL ratio method (CAR, KAP, NPM, ROA&BOPO, LDR). Findings: The results of the research in the last 3 years after being measured by the applicable standard Bank Indonesia regulations, it was found that the average soundness level of state-owned banks was in the Unhealthy Predicate. State-owned banks should improve their financial performance to increase the title as a healthy or very healthy bank because SOEs are banks that have the largest assets in Indonesia. Practical implications: Increasing the predicate as a healthy or very healthy bank because BUMN is the bank that has the largest assets in Indonesia. Originality/value: This paper is genuine paper type: research paper